2015
DOI: 10.1007/s11557-015-1079-2
|View full text |Cite
|
Sign up to set email alerts
|

Cantharellus cyphelloides (Cantharellales), a new and unusual species from a Japanese evergreen broad-leaved forest

Abstract: We describe a new species, Cantharellus cyphelloides (Cantharellaceae, Cantharellales, Agaricomycetes), from a Japanese evergreen broad-leaved forest based on morphological and molecular data. The new species differs from other Cantharellus species by its cyphelloid basidiomata with the hymenophore produced on the adaxial surface (inner side of the cup), rather than the abaxial surface. Molecular phylogenetic reconstruction, based on partial nLSU rDNA sequence data, and microscopic features place the new speci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 48 publications
0
4
0
Order By: Relevance
“…Cantharellus and based on a 100 base pair deletion in the internal transcribed spacer 1 (ITS1) of the rDNA (Ogawa et al 2018). Obtained tef-1 sequence data from all of our recent collections of chanterelles in South Korea could not confirm the presence of any of the European or North American Cantharellus previously reported from South Korea (Park and Lee 1991;Kim 2004;Kim et al 2006;Lee 2011) nor any of the chanterelles already described from India (Das et al 2015;Kumari et al 2011Kumari et al , 2013, neighbouring China (Shao et al 2011(Shao et al , 2014(Shao et al , 2016aTian et al 2012;, Japan (Suhara and Kurogi 2015;Ogawa et al 2018) or Malaysia (Corner 1966;Eyssartier et al 2009) Materials and methods…”
Section: Introductionmentioning
confidence: 72%
“…Cantharellus and based on a 100 base pair deletion in the internal transcribed spacer 1 (ITS1) of the rDNA (Ogawa et al 2018). Obtained tef-1 sequence data from all of our recent collections of chanterelles in South Korea could not confirm the presence of any of the European or North American Cantharellus previously reported from South Korea (Park and Lee 1991;Kim 2004;Kim et al 2006;Lee 2011) nor any of the chanterelles already described from India (Das et al 2015;Kumari et al 2011Kumari et al , 2013, neighbouring China (Shao et al 2011(Shao et al , 2014(Shao et al , 2016aTian et al 2012;, Japan (Suhara and Kurogi 2015;Ogawa et al 2018) or Malaysia (Corner 1966;Eyssartier et al 2009) Materials and methods…”
Section: Introductionmentioning
confidence: 72%
“…Molecular phylogeny has delimited abundant species within the genus and revealed unexpected species diversity ( Buyck et al, 2011 , 2013 , 2014 , 2016a , b ; Foltz et al, 2013 ; Leacock et al, 2016 ). Until now, a large number of Cantharellus taxa have been described in Europe, Africa, and North America ( Corner, 1966 ; Buyck et al, 2011 , 2013 , 2014 , 2016a , b , 2018 ; Kumari et al, 2011 , 2013 ; Suhara and Kurogi, 2015 ; De Kesel et al, 2016 ; Leacock et al, 2016 ).…”
Section: Introductionmentioning
confidence: 99%
“…At present, while updates on Cantharellus taxonomy have progressed relatively quickly in western Europe and North America, that in Asia remains very fragmented. However, recent studies have reported several new chanterelles from China (Shao et al, 2011;Tian et al, 2012;Shao et al, 2014Shao et al, , 2016aAn et al, 2017;Jian et al, 2020), Japan (Suhara and Kurogi, 2015;Ogawa et al, 2018), Korea (Antonin et al, 2017;Buyck et al, 2020), Malaysia (Eyssartier et al, 2009;Buyck et al, 2014), India (Das et al, 2015;Buyck et al, 2018), and Iran (Parad et al, 2018). Recently, a large-scale survey of wild edible mushrooms in local markets in Yunnan province, southwestern China, revealed that there was at least one cryptic species within this group of species in this region (Zhang et al, 2021).…”
Section: Introductionmentioning
confidence: 99%